2021
DOI: 10.3390/ijerph18189530
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Extrusion vs. Surgical Extrusion to Rehabilitate Severely Damaged Teeth: A Literature Review

Abstract: The need to rehabilitate severely compromised teeth is frequent in daily clinical practice. Tooth extraction and replacement with dental implant represents a common treatment choice. However, the survival rate for implants is inferior to teeth, even if severely damaged but properly treated. In order to reestablish a physiological supracrestal tissue attachment of damaged teeth and to arrange an efficient ferrule effect, three options can be considered: crown lengthening, orthodontic extrusion and surgical extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 63 publications
(145 reference statements)
0
20
0
7
Order By: Relevance
“…The orthodontic extrusion time is described with an average of four to six weeks and a retention period is recommended for four weeks up to six months 18 . One literature stated review that orthodontic extrusion is indicated in cases which request a highly predictable treatment, when an orthodontic device is already present, or tooth vitality should be preserved 15 . Although magnetic extrusion is described in individual case reports, no relevant reviews are currently available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The orthodontic extrusion time is described with an average of four to six weeks and a retention period is recommended for four weeks up to six months 18 . One literature stated review that orthodontic extrusion is indicated in cases which request a highly predictable treatment, when an orthodontic device is already present, or tooth vitality should be preserved 15 . Although magnetic extrusion is described in individual case reports, no relevant reviews are currently available.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical extrusion has been described as a viable treatment option in the management of teeth with insufficient residual substance, 15,20,21,25,29 although the level of evidence is very low since the available studies are often only case reports and case series. The advantages include minimum chair-side time compared with other procedures, good esthetics, ready acceptance from the patient, and low incidence of failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of a great amount of intact tooth structure to obtain a "ferrule effect" should be ensured by conducting a supracrestalfiberotomy, in combination with extrusion, to prevent coronal migration of the gingiva and bone. The fracture resistance of the tooth absolutely requires 1.5-2 mm of sound supragingival tooth structure [16] .Once the biologic width (around 2 mm) is established, the orthodontic treatment should stop, and the tooth should be stabilized for 6 weeks before restorative treatment [5,17] .…”
Section: Orthodontics and Endodonticsmentioning
confidence: 99%
“…The retention of extruded tooth structure is equally very important. The duration of extrusion should be the duration of minimum retention period 49 .…”
Section: Orthodontic Extrusion Of Traumatic Teethmentioning
confidence: 99%